2008
DOI: 10.3109/10929080802364645
|View full text |Cite
|
Sign up to set email alerts
|

Real-time MRI-TRUS fusion for guidance of targeted prostate biopsies

Abstract: Targeted prostate biopsy is challenging because no currently established imaging modality is both accurate for prostate cancer diagnosis and cost-effective for real-time procedure guidance. A system that fuses real-time transrectal ultrasound images with previously acquired endorectal coil MRI images for prostate biopsy guidance is presented here. The system uses electromagnetic tracking and intraoperative image registration to superimpose the MRI data on the ultrasound image. Prostate motion is tracked and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
220
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 276 publications
(225 citation statements)
references
References 13 publications
1
220
1
3
Order By: Relevance
“…Thus, there may have been a selection bias against lesions that were not depicted on T2-weighted MR images and ADC maps. Second, results from MR imaging-transrectal US fusion-guided biopsy were used as the reference standard for validation instead of whole-mount histopathologic maps; however, this system has been found to be accurate (2.4 mm 6 1.2) in phantom and canine studies ( 29 ). Additionally, although the box and whisker plots demonstrate a substantial overlap in ADCs of different Gleason scores and D'Amico clinical risk scores, our statistical analysis indicates that ADCs can be used to differentiate tumors with higher Gleason scores and intermediate to high clinical risk scores from those with lower scores.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there may have been a selection bias against lesions that were not depicted on T2-weighted MR images and ADC maps. Second, results from MR imaging-transrectal US fusion-guided biopsy were used as the reference standard for validation instead of whole-mount histopathologic maps; however, this system has been found to be accurate (2.4 mm 6 1.2) in phantom and canine studies ( 29 ). Additionally, although the box and whisker plots demonstrate a substantial overlap in ADCs of different Gleason scores and D'Amico clinical risk scores, our statistical analysis indicates that ADCs can be used to differentiate tumors with higher Gleason scores and intermediate to high clinical risk scores from those with lower scores.…”
Section: Discussionmentioning
confidence: 99%
“…Needle trajectories were mapped with real-time electromagnetic tracking in the biopsy platform (Northern Digital, Ontario, Canada). Results of previous validation studies have indicated an accuracy of within 3 mm for this platform (11).…”
Section: Mr Image Interpretationmentioning
confidence: 99%
“…Detecting tumors in the CG is more complex because the CG becomes progressively larger and more heterogeneous with age; CG tumors are defined as homogenous, low-signal-intensity lesions with irregular margins and without a capsule. They often invade the pseudocapsule or of MRI data during biopsies (e.g., TRUS-MRI fusion for guidance) can potentially decrease the number of patients undergoing unnecessary prostate biopsies and increase the yield of those who do, but the cost-effectiveness of this approach has not been demonstrated (23) (Fig. 6).…”
Section: Mri For Screening Before a Trus-guided Biopsymentioning
confidence: 99%